Progress in Additive Manufacturing 2020 2022
DOI: 10.1520/stp163720200125
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Mechanical Properties of AISI 4140 Steel Processed by Electron Beam Powder Bed Fusion Analyzed Using Miniature Samples

Abstract: The present study reports on the identification of an adequate process window for electron beam powder bed fusion (E-PBF) of AISI 4140 steel. For characterization, only miniature samples were used. It is clearly revealed that, for comparison and evaluation of different conditions, the use of such small samples is absolutely sufficient, even under fatigue loading. The initial E-PBF as-built condition is compared with conventionally heat-treated conditions (i.e., normalized as well as quenched and tempered). Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…42CrMo4 powder produced by TLS Technik GmbH & Co Spezialpulver KG (Bitterfeld-Wolfen, Germany) was used. Details concerning the powder are given in [ 14 ]. The samples were produced in form of cubes with an edge length of 10 mm on support structures (height 5 mm, type: block supports) under an argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…42CrMo4 powder produced by TLS Technik GmbH & Co Spezialpulver KG (Bitterfeld-Wolfen, Germany) was used. Details concerning the powder are given in [ 14 ]. The samples were produced in form of cubes with an edge length of 10 mm on support structures (height 5 mm, type: block supports) under an argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…A wide variety of materials, e.g., titanium-, aluminum-, nickel-, or copper-based alloys, and also steels such as H13 or 17-4PH, have been successfully processed via PBF-LB/M and PBF-EB/M. In the context of manufacturing the low-alloyed Q&T steel 42CrMo4 via powder bed-based AM techniques, studies using the PBF-EB/M process are still limited; only two studies [ 1 , 14 ] can be found in the open literature. In contrast, several studies available have focused on PBF-LB/M-processed 42CrMo4 [ 15 , 16 , 17 , 18 ], revealing that the process is capable of producing parts of low porosity.…”
Section: Introductionmentioning
confidence: 99%